Separação de níquel a partir de soluções sulfúricas contendo cálcio e magnésio utilizando-se sistemas aquosos bifásicos - Leandro Henrique Santos (2014)
The selective extraction of metals from sulfuric aqueous solutions simulating leaching liquors of lateritic ores containing nickel, calcium and magnesium employing the technique Aqueous Biphasic Systems using extractants Cyanex 272, PAN and 1N2N in SAB L64 + tartrate sodium, L64 + sodium sulfate and L64 + sodium citrate, was investigated in this work. The main objective was to extract selectively the metals present in the synthetic liquor in order to obtain a solution of higher purity. The extraction tests were carried out at room temperature, keeping the ratio of the upper and lower phases weight as unit. During the evaluation of the operating variables step, the pH of the aqueous phase was varied from 1.00 to 11.00, and a dilution factor of approximately 80 times over the original synthetic liquor was applied. The liquor was pre-purified with respect to Ca, in one single stage extraction at pH = 11.00 in the absence of extractant with L64 + sodium tartrate, so that remained in the raffinate about 89.0% of nickel and 92.7% of magnesium. The purification relative to magnesium was obtained under the same conditions in the presence of 20 mmol.kg-1 of 1N2N, considering 3 extraction stages, remaining approximately 68.0% of magnesium, with extraction of 90.0% of nickel. During the tests using the concentrate synthetic liquor (original solution), the pre-purification on calcium were obtained at pH 2.00 in the absence of extractant, considering three extraction stages, leaving about 95.2% of nickel and 99.9% of magnesium in the raffinate. The purification relative to the magnesium under the same conditions and in the presence of 20 mmol.kg-1 of 1N2N was not obtained efficiently, remaining approximately 86.1% of magnesium and 93.5% of nickel in the liquor, even after five stages of extraction.